Stability and dynamics of in-plane skyrmions in collinear ferromagnets - Zarzuela, Ricardo; Bharadwaj, Venkata Krishna; Kim, Kyoung-Whan; Sinova, Jairo; Everschor-Sitte, Karin (AMER PHYSICAL SOC, 2020)
We study the emergence and dynamics of in-plane skyrmions in collinear ferromagnetic heterostructures. We present a minimal energy model for this class of magnetic textures, determine the crystal symmetries compatible with it, and propose material candidates, based on symmetries only, for the observation of these topological solitons. We calculate exact solutions of the energy model for in-plane skyrmions in the absence of dipolar interactions at critical coupling, the latter defined by the relations H = K and D = root AK for the strength of the external magnetic field and the Dzyaloshinskii coupling constant, respectively, with K and A being the anisotropy constant and the exchange stiffness of the material. Through micromagnetic simulations we demonstrate the possibility of in-plane skyrmion production via (i) the motion of domain walls through a geometrical constriction and (ii) shedding from a magnetic impurity driven both by spin transfer torques. In-plane skyrmion dynamics triggered by spin-orbit torques are also investigated analytically and numerically. Our findings point towards the possibility of designing racetracks for in-plane skyrmions, whose speed could be tuned by adjusting the angle between the charge current and the uniform background magnetization; in particular, the speed is maximum for currents parallel to the easy axis and becomes zero for currents transverse to it.
Keywords: MAGNETIC SKYRMIONS; MOTION